The United Nations Security Council’s Sanctions against Iran: A Nuclear Apartheid - Eishan Jan, Mohammad Naqib (LexisNexis, 2007)
On 23rd December 2006 the United Nations Security Council unanimously decided to pass Resolution 1737 imposing what is known as ‘smart sanction’ against Iran - a sanction that demands Iran to end all of its uranium enrichment activities; orders all countries to stop supplying Iran with materials and technology that could contribute to its nuclear and missile program; and freeze Iranian assets of key companies and individuals related to those programs. Since Iran did not abide by Resolution 1737, on 24th March 2007 the Security Council passed a new resolution (Resolution 1747) imposing slightly tougher sanctions including blocking Iranian arms exports and freezing the assets of 28 people and organizations involved in Iran's nuclear and missile programs. These decisions of the Security Council, which were adopted under Chapter VII of the United Nations Charter, are ‘non-military’ enforcement actions binding on all States by virtue of Article 25 of the Charter. The decisions raise a number of issues: Are these decisions inline with purposes and principles of the United Nations (UN) as laid down in its Charter? Is there any international judicial authority to review the decision of the Security Council in this regard? Even if there is no such authority, as this paper shows there is none, the Security Council is still obliged to abide by its obligation under the Charter, correctly follow the procedures laid down in it and take enforcement action against a State whose acts has threatened international peace and security. The question here is: Is there any clear evidence to show Iran’s nuclear activities a threat to international peace and security? If there is no such evidence, as this paper shows there is none and that Iran has not breached its treaty or any other of its obligations under international law, why is it then Iran - not other nuclear producing counties like India, Pakistan and Israel - selected for such a sanction? Is the UN Security Council, by imposing these sanctions against Iran, legitimizes the ‘nuclear apartheid’ practiced by certain Western countries? Why certain countries, like the United States, United Kingdom, France, Russia and China allowed to own nuclear weapons while other countries are not? Is it not a ‘nuclear apartheid’? Surely, it is, as this paper concludes. It is an apartheid that has been given legal form in the 1970 Nuclear Non-Proliferation Treaty (NPT). This paper further concludes that since Iran neither breached its obligation under the NPT nor its nuclear activities can be considered a threat to international peace and security the legitimacy of the Security Council’s decisions against Iran are legally questionable decisions.